EFEKTIVITAS MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN MEDIA SCRAPBOOK DILENGKAPI LKS TEKA-TEKI SILANG TERHADAP HASIL BELAJAR SISWA DI SMA PGRI WAINGAPU - Loda Hamu, Asniyanti; Tamu Ina, Anita; Hada Enda, Riwa Rambu; Ndapa Huda, Marleni Rosalia (Jurnal Biogenerasi, 2024)
This study aims to determine the influence of the STAD-type cooperative learning model assisted by Scrapbook media and equipped with crossword puzzle LKS on the growth and development of living things at SMA PGRI Waingapu. This type of research is quantitative and uses an experimental approach. Sampling was carried out by purposive sampling technique. There are two classes used, namely class XII MIPA 1 as a control class and class XII MIPA 3 which is used as an experimental class. The data analysis techniques used were validity, reliability, homogeneity, normality and hypothesis tests using independent sample t-testi. Based on the research, the results of the pretest and posttest were obtained for the control class of 47.07 and 78.84 while for the experimental class of 51.84 and 84.27. The hypothesis test showed an Asym Sig. (2-tailed) value of 0.001, which showed that the use of the STAD model assisted by Scrapbook media and equipped with crossword puzzle LKS had a significant influence on the learning outcomes of students at SMA PGRI Waingapu. Keywords: STAD, Scrapbook, Crossword puzzles, Student learning outcomes